Utilização da farinha de resíduos de acerola e umbu cajá na produção de bolo tipo cupcake - Silva, Denise Andrade da (2017)
Several sectors of society have now concentrated their efforts on finding means to make compatible the levels of economic growth and production, with the maintenance of environmental quality and the preservation of natural, material and energy resources. In this context, the development of techniques aimed at minimizing environmental impacts, especially in relation to waste produced by the agroindustry, can reduce the impact of economic activity on the environment, such as the use of these wastes in the generation of new products with higher added value, For human consumption. The objective of this thesis was to evaluate the potential of pulp residues of acerola and umbu cajá in the elaboration of food flours with application in the production of cupcake type cakes. The collected residues, food flours and cupcakes were characterized by the physical-chemical parameters (acidity, pH, soluble solids, vitamin C, lipids, water activity, moisture, ashes, protein and carbohydrates) and microbiological parameters (Coliformes at 45ºC, Salmonella and mold and yeast). To obtain the flour, two drying temperatures (60ºC and 70ºC) were adopted. The analysis of minerals (sodium, potassium, calcium, iron, manganese, copper and zinc) was carried out with the purpose of analyzing the effect of the temperatures adopted on the nutritional constituents. Cupcake cakes were processed in a total of five formulations: 5% (Type I), 10% (Type II), 15% (Type III) and 20% (Type IV) Of wheat (in relation to the total weight of the wheat flour) and the standard formulation without the addition of flour. The quality of the cakes was evaluated through physical-chemical, microbiological and sensorial parameters (acceptance test and purchase intention) in addition to shelf-life analysis. The results showed that at 60ºC drying temperature the nutritional constituents had a stable behavior when compared to the temperature of 70ºC. The results of the sensorial evaluation showed that levels of up to 20% of the addition of the acerola residue meal and umbu cajá presented satisfactory scores on the sensorial attributes evaluated. Thus, formulations containing 20% of FRA and FRU were selected for the other analyzes. It was observed that with the increase of FRA and FRU proportions in relation to wheat flour, there was a reduction in the energy value and the proportion of carbohydrates in the formulation containing 20%. There was no significant difference between the values of moisture, ashes, proteins and lipids. The storage of the cakes was satisfactory in a period of 7 days. It can be concluded that the residues meal of acerola and umbu cajá can be added in products such as cakes and the like, being able to be offered to the consumers, reducing the waste of food, also presenting good possibility of industrialization.